Modeling of semi-active magnetorheological damper for automobile suspension system - Rahman, Mahmudur (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
The design of vehicle suspension systems is an active research field in which one of the objectives is to improve the passenger's comfort through the vibration reduction of the internal engine and external road disturbances. Comfort and road handling in car can be improved by including a semi-active suspension system, controlled by varying the damping based on measurements of the vehicle motions. This research deals with design and development of a quarter-car suspension using magneto-rheological damper (MR). A quarter-car of two degree-of-freedom (DOF) system is designed and constructed on the basis of the concept of a four-wheel independent suspension to simulate the actions of a semi-active vehicle suspension system. The selection of an appropriate MR damper model is crucial, since it provides the suitable current and force relationship and allows finding the appropriate force to the system. The behavioral characteristic of selected MR damper model is simulated and analyzed with different current input. An effective control structure is a key function of this research to determine the complexity of the control design and parameter tuning process. The performance of Proportional Integral Derivative (PID) and Linear Control Regulator (LQR) controller is designed based on the system requirements. In this research, the PID controller is verified experimentally under different road excitations to improve the ride quality and vehicle safety.